Abdulsalam Ibraheem Rafida: Sorrow for Your Loss - Atia, Ahmed (AlQalam Journal of Medical and Applied Sciences, 2021)
On April 10, 2021, colleges, friends, and students of University of Tripoli were shocked by news of death of Abdulsalam Ibraheem Rafida, Professor of Analytical Chemistry at Faculty of Medical Technology, the University of Tripoli. He died in a Turkey hospital after a short struggle with leukemia and bone marrow cancer, with subsequent Covid-19 infection, caused Severe Respiratory Distress Syndrome (SARS). Professor Abdulsalam was born in Tripoli on January 27, 1962. He obtained his BSc in 1984 and MBBS in 1994 from the University of Tripoli. He received his PhD in 2006 from University of Newcastle upon Tyne, UK. His PhD thesis in environmental biotechnology was on the removal of heavy metals in vertical flow biofilters conditioned with sulphate reducing bacteria (SRB).